Analisis Pemanfaatan Educaplay dalam Asesmen Diagnostik Digital Kesiapan Bersekolah Anak Usia 4–5 Tahun: Analysis of the Use of Educaplay in Digital Diagnostic Assessment of School Readiness for Children Aged 4–5 Years - Anggi Oktaviani Rizka Sulaikha; Maria Qori’ah; Viena Wanidha Andriani; Ria Octa Viana; Riris Wahyuningsih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Diagnostic assessment plays a crucial role in identifying school readiness in early childhood, serving as a foundation for designing instruction that aligns with developmental needs. However, assessment practices in many early childhood education (ECE) institutions remain dominated by conventional methods that fail to yield comprehensive developmental information or adapt to technological advancements. This study aims to analyse the use of Educaplay as a digital diagnostic assessment tool to identify school readiness among 4–5-year-old children at RA Baitussalam Toyamas (Wringinrejo, Gambiran, Banyuwangi) during the 2025/2026 academic year. A qualitative approach with a case study design was employed. Research informants—comprising the school principal, teachers, and parents—were selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analysed using the interactive model developed by Miles, Huberman, and Saldaña, which encompasses data condensation, data display, and conclusion drawing/verification. The results indicate that Educaplay transforms assessment practices from mere developmental measurement activities into a more systematic, interactive process of mapping school readiness that is oriented toward children's developmental needs. The findings also construct a "Digital Assessment for Learning" perspective, wherein digital diagnostic assessment is utilised to generate authentic developmental evidence as a basis for pedagogical decision-making. The implementation of digital assessment is influenced by teachers' pedagogical competence, children's developmental characteristics, institutional support, and collaboration with parents. This study contributes conceptually to the development of digital diagnostic assessment in early childhood education. It serves as a reference for ECE institutions seeking to develop assessment practices that are more adaptive, authentic, and centred on child development.